2010
DOI: 10.1002/cncr.25465
|View full text |Cite
|
Sign up to set email alerts
|

Obesity adversely affects survival in pancreatic cancer patients

Abstract: BACKGROUND: Higher body-mass index (BMI) has been implicated as a risk factor for developing pancreatic cancer, but its effect on survival has not been thoroughly investigated. The authors assessed the association of BMI with survival in a sample of pancreatic cancer patients and used epidemiologic and clinical information to understand the contribution of diabetes and hyperglycemia. METHODS: A survival analysis using Cox proportional hazards by usual adult BMI was performed on 1861 unselected patients with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 73 publications
5
54
4
Order By: Relevance
“…This approach has been proposed as a remedy for such situations and its incorporation into routine practice has been recommended to avoid biased estimates [17, 21, 22]. Also, the absolute number of obese and very obese patients (BMI >30) in our Swiss cohort was much lower (N = 32; 7%, Table  1) as compared to previously published US cohorts [10]. Second, we had no data on the development of BMI or onset of diabetes during therapy and follow-up.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This approach has been proposed as a remedy for such situations and its incorporation into routine practice has been recommended to avoid biased estimates [17, 21, 22]. Also, the absolute number of obese and very obese patients (BMI >30) in our Swiss cohort was much lower (N = 32; 7%, Table  1) as compared to previously published US cohorts [10]. Second, we had no data on the development of BMI or onset of diabetes during therapy and follow-up.…”
Section: Discussionmentioning
confidence: 76%
“…Recently high baseline serum concentration of the tumour marker CA 19–9 has been identified as an independent negative prognostic factor in two independent cohorts of patients with advanced pancreatic cancer [8, 9]. There is some evidence that men have an increased risk of death compared to women [9], however this association was not confirmed by another group [10]. Obesity at the time of diagnosis has been reported to be associated with worse prognosis in several malignant diseases including prostate, colon, and breast cancer [1113] – an observation with major implications given the epidemic prevalence of obesity in many regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Carrying a disease-associated mutation in the CFTR gene has been recently linked to a modest increased risk for developing pancreatic cancer [42]. Another report [43] does not support the view that CFTR mutations and the 5T allele conferred a higher risk of pancreatic cancer, although a review [44] has concluded a modest but consistent increased risk of pancreatic cancer in CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among studies investigating obesityrelated prognosis in all stages of pancreatic cancer, 1 retrospective review of 475 patients found no difference among patients with both resectable and nonresectable diseases, 23 although other studies reported that obesity was associated with worsening clinical outcome. 10,24 In patients who have undergone curable resection for early stage pancreatic cancer, the impact of obesity again has been even more controversial. One retrospective study reviewed 306 patients undergoing pancreatic resection and found that, although obese patients were more likely to experience postoperative complications (P = 0.01), there was no significant difference seen in overall survival.…”
mentioning
confidence: 99%